Saying sorry – should a ‘safe space’ be created to allow effective communication between healthcare practitioners and aggrieved parties after an iatrogenic event in South Africa? - M S Khan; M C Laubscher (South African Medical Journal)
The incidence of medical negligence claims is well documented in South Africa (SA). Civil and criminal processes are in place to deal with this, and the matter may be reported to the Health Professions Council of SA (HPCSA). There is a school of thought that suggests that these processes do not provide sufficient relief to an affected party. The processes are not always satisfactory; an aggrieved party may wish to know the reasons why a particular error occurred and why a healthcare practitioner acted in a particular manner. In addition to this, they may want to receive a sincere apology. Medical practitioners may also want to communicate with patients or family members of a patient who has passed away as a result of an iatrogenic event, but may be fearful of litigation. This article considers the current position in SA in relation to issuing an apology related to an iatrogenic event, and consults foreign jurisdictions for further guidance on the topic.